An empirical analysis of technology absorption capacity of the Brazilian industry - Pablo Felipe Bittencourt; Ricardo Giglio (CEPAL Review, 2013)
This article presents and discusses empirical evidence on external technology absorption facilitated by activities performed inside firms. Indicators of internal and external learning are developed and applied in statistical causality models, to distinguish possible ways in which technology can be absorbed. Industrial activity sectors at the three-digit level of the National Classification of Economic Activities (nace) are the basic reference units of the research, which uses the information generated by Brazil’s Survey of Technological Innovation (pintec). The results show that in-house research and development (r&d) is the main source of technology absorption, followed by the knowledge generated from the “learning by doing” and “training practices”.